New global ICT-based business models - Lindgren, Peter (River Publishers, 2011)
The New Global Business model (NEWGIBM) book describes the background, theory references, case studies, results and learning imparted by the NEWGIBM project, whichis supported by ICT, to a research group during the period from 2005-2011.